Identification of Enterococcus isolated from whey of artisanal cheeses from Puebla - Alvarado-Castillo, Ma. Gabriela; Montalvo-Paquini, Claudia; Baltazar-Gómez, Guadalupe; Ortega-Cadena, Omar; Camacho-Martínez, Francisco Javier; Borraz-Arguello, María del Tránsito (Ecosistemas y Recursos Agropecuarios, 2024)
Mexico’s cheese artisanal production is similar or higher than industrial production, approximately 100 L cow’s milk are used to made 10 Kg of cheese and 90 L of whey, that could be considered like an environmentally harmful by product because it has a high content of organic matter that promotes the growth and development of Enterococcus. In this study, Enterococcus strains were identified in whey from four locations of Puebla. Bacterial gram positive were isolated, furthermore their metabolism shown negative catalase, growth at different temperature (10, 40 and 45 °C), pH values (9.2 and 9.6) and NaCl concentrations (4 and 6.5%). Endpoint PCR tests were made to confirm detection of Enterococcus faecium(19 strains) and Enterococcus faecalis (six strains) in whey from three locations, these results suggest that a better sanitary control of whey is necessary to avoid the proliferation of potentially pathogenic microorganisms.
Keywords: isolation; lactic acid bacteria; Enterococci; phenotypic identification; molecular identification